PENGARUH MODEL ARIAS (ASSURANCE, RELEVANCE, INTEREST, ASSESSMENT, SATISFACTION) TERHADAP KEMAMPUAN MENULIS TEKS EKSPLANASI PADA SISWA KELAS XI SMA SWASTA NASIONAL PETATAL - Rafika Muspita Sari; Susi Masniari Nasution; Karimaliana Karimaliana; Intan Permata Sari (Smart Education, 2025)
Abstract: This research aims to determine the effect of the ARIAS (Assurance, Relevance, Interest, Assessment, Satisfaction) model on the ability to write explanatory texts in class XI students at Petatal National Private High School.